Sex Determination from Fragmented and Degenerated DNA by Amplified Product-Length Polymorphism Bidirectional SNP Analysis of Amelogenin and SRY Genes - Masuyama, Kotoka (PLoS One, 2017)
Sex determination is important in archeology and anthropology for the study of past societies, cultures, and human activities. Sex determination is also one of the most important components of individual identification in criminal investigations. We developed a new method of sex determination by detecting a single-nucleotide polymorphism in the amelogenin gene using amplified product-length polymorphisms in combination with sex-determining region Y analysis. We particularly focused on the most common types of postmortem DNA damage in ancient and forensic samples: fragmentation and nucleotide modification resulting from deamination. Amplicon size was designed to be less than 60 bp to make the method more useful for analyzing degraded DNA samples. All DNA samples collected from eight Japanese individuals (four male, four female) were evaluated correctly using our method. The detection limit for accurate sex determination was determined to be 20 pg of DNA. We compared our new method with commercial short tandem repeat analysis kits using DNA samples artificially fragmented by ultraviolet irradiation. Our novel method was the most robust for highly fragmented DNA samples. To deal with allelic dropout resulting from deamination, we adopted “bidirectional analysis,” which analyzed samples from both sense and antisense strands. This new method was applied to 14 Jomon individuals (3500-year-old bone samples) whose sex had been identified morphologically. We could correctly identify the sex of 11 out of 14 individuals. These results show that our method is reliable for the sex determination of highly degenerated samples.